2024
DOI: 10.3390/ma17010246
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Spectral Properties of Novel 2-Mercaptobenzothiazole Derivatives

Agnieszka Skotnicka,
Janina Kabatc-Borcz

Abstract: This paper is focused on the optimalization of methods for the synthesis, isolation, and purification of 2-mercaptobenzothiazole-based acrylic and methacrylic monomers. The structures of the newly synthesized compounds were confirmed through infrared (IR) and nuclear magnetic resonance spectroscopy (NMR). Spectroscopic properties of the resulting 2-mercaptobenzothiazole derivatives were determined based on their absorption spectra and molar absorption coefficients in solvents with varying polarities. A correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is shown that the average sliding friction coefficient of UHMWPE decreased to 34% after filling with CuO nanoparticles, and the wear mechanism changed from adhesive wear to fatigue wear. 2-mercaptobenzothiazole (MBT) is a bicyclic heteroatomic molecule that is used as a rubber vulcanization accelerator and is widely used in the production of tires, rubber shoes, and other rubber products [26]. We have previously investigated the effect of wollastonite and 2-mercaptobenzothiazole on the mechanical and tribological properties of UHMWPE [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the average sliding friction coefficient of UHMWPE decreased to 34% after filling with CuO nanoparticles, and the wear mechanism changed from adhesive wear to fatigue wear. 2-mercaptobenzothiazole (MBT) is a bicyclic heteroatomic molecule that is used as a rubber vulcanization accelerator and is widely used in the production of tires, rubber shoes, and other rubber products [26]. We have previously investigated the effect of wollastonite and 2-mercaptobenzothiazole on the mechanical and tribological properties of UHMWPE [27].…”
Section: Introductionmentioning
confidence: 99%